2018
DOI: 10.1016/j.bbadis.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

4-PBA ameliorates cellular homeostasis in fibroblasts from osteogenesis imperfecta patients by enhancing autophagy and stimulating protein secretion

Abstract: The clinical phenotype in osteogenesis imperfecta (OI) is attributed to the dominant negative function of mutant type I collagen molecules in the extracellular matrix, by altering its structure and function. Intracellular retention of mutant collagen has also been reported, but its effect on cellular homeostasis is less characterized. Using OI patient fibroblasts carrying mutations in the α1(I) and α2(I) chains we demonstrate that retained collagen molecules are responsible for endoplasmic reticulum (ER) enlar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 59 publications
(82 reference statements)
8
86
0
Order By: Relevance
“…Procollagen is degraded mainly in lysosomes but some of collagen mutant chains can be degraded in proteasomes . Interestingly, UPR induction due to retention of mutated collagen type I chains in ER was reported . Therefore, there is an open question whether impairing of collagen secretion may contribute to NEL‐induced ER stress in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Procollagen is degraded mainly in lysosomes but some of collagen mutant chains can be degraded in proteasomes . Interestingly, UPR induction due to retention of mutated collagen type I chains in ER was reported . Therefore, there is an open question whether impairing of collagen secretion may contribute to NEL‐induced ER stress in fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…For example, with collagen I mutations in OI clear evidence of UPR activation was demonstrated for a procollagen I C‐propeptide trimerization mutation in the Aga2/+ mouse with upregulation of BiP, Hsp47, and Gadd153 (Chop) resulting in osteoblast apoptosis (Lisse et al, ). Recent studies on patient collagen I helix mutations reported upregulation of several components of the UPR, including BiP, PDI, ATF4, phospho‐PERK and XBP1 splicing (Besio et al, ). However, the pattern of upregulation of these individual UPR components was different in the five patient mutations studied.…”
Section: Is Er Stress a Driver Of Pathology With Ecm Protein Structurmentioning
confidence: 99%
“…However, the pattern of upregulation of these individual UPR components was different in the five patient mutations studied. For example, BiP was upregulated in only three of five COL1A1 or COL1A2 mutations tested (Besio et al, ), highlighting that while a UPR can be activated by these mutations, there is apparent mutation specificity in the strength and nature of the response. In a mouse model of mild to moderate OI due to a Col1a2 missense mutation (α2(I) G610C) which disturbs the collagen triple helix, ER accumulation of the mutant misfolded collagen I results in upregulation of CHOP, eiF2α phosphorylation, and chaperones αβ crystalline and HSP47, and it was concluded this ER‐stress did not involve the canonical UPR pathway (Mirigian et al, ).…”
Section: Is Er Stress a Driver Of Pathology With Ecm Protein Structurmentioning
confidence: 99%
See 1 more Smart Citation
“…TGFbeta [16,17]) and chemical stimulants (e.g. ascorbic acid [17][18][19], glycolic acid [20], 4-phenyl butyric acid (4-PBA) [21] and retinol [22]) to boost the collagen production and matrix deposition. However, these molecules have multiple other roles in the body and the therapies are associated with negative side effects, such as promoting abnormal angiogenesis, or inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%